Aquaculture: To Achieve Economic Development in Bihar, India-A Review - Bharti, Vivekanand; Sarma, Kamal; Kumar, Tarkeshwar; Singh, Jaspreet; Ahirwal, Surendra Kumar (International Journal of Bio-resource and Stress Management, 2022)
The contribution of aquaculture and fisheries to Gross Domestic Product (GDP) is considered as one of the most important indicators for assessing the economic performance of the country. A large section of Bihar’s population relies on agriculture, animal husbandry, and fishing for their livelihood. The fisheries sector plays a critical role in ensuring nutritional security and creating employments. The culture and consumption of fish therefore has important implications for national income and food security. Bihar’s entire fish output in 2019 was estimated 0.64 mt, contributing 1.5% of the State’s total Gross Domestic Product (SGDP). However, the occurrence of annual saga in terms of floods and drought, rather than lack of recent advancement in aquaculture are the major challenges for the development of aquaculture in Bihar. Despite the fact that the state’s momentum in aquaculture over the last decade propelled it to fourth place in inland fish production and sixth place in freshwater seed production in India. The substantial investments in fisheries sector in the State can improve the income of farmers. The State’s aquaculture production can be further enhanced by harnessing the bestowed fishery resources at a sustainable level with approaches for acceleration in fish production such as promotion of aquaculture in wetlands, species and technological diversification for aquaculture, extension of improved aquaculture technology, realization the scope of integrated fish farming, establishing of fish hatchery, assembling of fish market and supply chain and propagation of ornamental fish activities.